Metaphoric extension of the thermodynamic entropy - Olano, Servillano S.B., Jr. (Animo Repository, 1998)
Dr. Servillano Olano, Chemical Engineering faculty and La Salle Fellow, delivered the lecture, Metaphoric Extension of the Thermodynamic Entropy. The lecture wais also part of the Mission Statement-University Week celebration.